2010
DOI: 10.1007/s10658-010-9718-6
|View full text |Cite
|
Sign up to set email alerts
|

Using metabolic profiling to assess plant-pathogen interactions: an example using rice (Oryza sativa) and the blast pathogen Magnaporthe grisea

Abstract: A metabolomics based approach has been used to study the infection of the Hwacheong rice cultivar (Oryza sativa L. cv. Hwacheong) with compatible (KJ201) and incompatible (KJ401) strains of the rice blast fungal pathogen Magnaporthe grisea. The metabolic response of the rice plants to each strain was assessed 0, 6, 12, 24, 36, and 48 h post inoculation. Nuclear Magnetic Resonance (NMR) spectroscopy and Gas and Liquid Chromatography Tandem Mass spectrometry (GC/LC-MS/MS) were used to study both aqueous and orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 31 publications
3
57
0
Order By: Relevance
“…These stresses also include sugar starvation and metabolism disorders caused by pathogen attack. Jones et al (2011) showed that in rice infested by Magnaporthe grisea sensitive cultivars had a lower level of metabolites involved in energy metabolism than cultivars resistant to that fungus. At a threat of cell energy deficit SnRK1 regulates the expression of over 1,000 genes, restoring cell homeostasis by repressing energy-intensive anabolic pathways and activating catabolism genes (Baena-Gonzalez 2010).…”
Section: Sugar Sensing and Signalingmentioning
confidence: 99%
“…These stresses also include sugar starvation and metabolism disorders caused by pathogen attack. Jones et al (2011) showed that in rice infested by Magnaporthe grisea sensitive cultivars had a lower level of metabolites involved in energy metabolism than cultivars resistant to that fungus. At a threat of cell energy deficit SnRK1 regulates the expression of over 1,000 genes, restoring cell homeostasis by repressing energy-intensive anabolic pathways and activating catabolism genes (Baena-Gonzalez 2010).…”
Section: Sugar Sensing and Signalingmentioning
confidence: 99%
“…Our group has been applying this technology to the detection and structure elucidation of metabolites in plants upon 105 treatment with a wide range of biotic and abiotic stress agents (Choi et al, 2004;Simoh et al, 2009;Jahangir et al, 2009;Mirnezhad et al, 2010;Simoh et al, 2010). In recent years, very detailed NMR metabolomic studies on both compatible and incompatible plant-pathogen interactions have been reported (Lima et al, 2010;Bollina et al, 2010;Ward et al, 2010;Jones et al, 2011). 110…”
Section: Introductionmentioning
confidence: 99%
“…The TSP was used as a reference at δ 0.00. The metabolites were identified based on the 1 H-NMR spectra and comparisons with the NMR spectra of the reference compounds and published literatures (Fan 1996;Dai et al 2010;Kim et al 2010;Jones et al 2011;Nuringtyas et al 2012;Nam et al 2015;Uawisetwathana et al 2015;Liu et al 2017;Pramai et al 2017).…”
Section: H-nmr Analysismentioning
confidence: 99%